ACHIEVEMENT-ORIENTED BEHAVIORAL PRACTICES BY THE HEAD OF RAUDHATUL ATHFAL IN THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM - Wiyani, Novan Ardy; Novi Mulyani (re-JIEM (Research Journal of Islamic Education Management), 2024)
This study aims to describe and analyze the practice of achievement-oriented behavior by the head of RA Nurul Dzikri towards teachers in the implementation of the independent curriculum. Theoretically, the practice of achievement-oriented behavior is one manifestation of the practice of path-goal leadership. This research uses a qualitative research approach with a phenomenological research type. Data was collected using interviews, observation, and documentation. Then the data were analyzed using the data analysis technique of the Miles and Huberman models, which consisted of three stages: data reduction, data display, and verification. The results showed that the practice of achievement-oriented behavior by the head of RA towards teachers in the implementation of the independent curriculum and moderation of religion at RA Nurul Dzikri was carried out through the following steps: (1) Identifying problems in the implementation of the independent curriculum and moderation of religion; (2) Make remedial efforts to overcome problems in implementing the independent curriculum and religious moderation; (3) Giving teachers space to be creative in implementing the independent curriculum and religious moderation; and (4) Providing opportunities for teachers to increase their competence in implementing the independent curriculum and religious moderation. These four steps have made teacher RA Nurul Dzikri gain achievements in implementing the independent curriculum by making it a national-scale benchmarking center for other early childhood education institutions in implementing the independent curriculum.